RANCANG BANGUN SISTEM PENGUKURAN PERGESERAN TANAH MENGGUNAKAN SENSOR VARIABEL RESISTOR - Sugito, Sugito; Hartono, Hartono; Permadi, Ipung (BERKALA FISIKA, 2015)
The phenomenon of ground motion are things that need serious attention. The impact that can be caused by the ground motion can not be underestimated. The velocity of ground motion at each area has different characteristics. Monitoring of ground motion continuously is one way to be able to determine the policy relating to protection measures. Variable resistor is a component that can be used to detect the presence of such a shift. Variable resistor connected to the shear plane using a cord will be amended proportionalÂ  with the shift in resistance value of shear plane. Variable resistor arranged with others resistor to form a Wheatstone bridge circuit. Thus the change in resistance on the variable resistor will produce a voltage change. Value of voltage changes were characterized to obtain the calibration equations, response time and stability of the sensor. Data acquisition is done by using a personal computer and the device interface DAQ NI USB6009. While programming created using LabView 7.1 software. Based on the results obtained by testing the sensor response time is very good sensor is equal to 0.47 seconds. Highly stable sensors to take measurements, look at the value of the average reading deviation of 1.14 %. The sensor has a measurement in the range of 0 to 17 cm. Keywords : variable resistor, sensor, Wheatstone bridge, characterization